STS Marker Associated with Iron Toxicity Tolerance in Rice - Chrisnawati, Lili (Journal of Tropical Life Science, 2016)
Iron (Fe) toxicity is one of the limiting factors for rice growth and production in paddy fields. The use of iron tolerant varieties is one of the most efficient way to solve this problems. Identification of molecular markers linked to the trait is very important to develop marker-assisted selection (MAS) to obtain tolerant lines. The objective of this study was to identify sequence tagged sites (STS) markers associated with iron tolerance trait in double haploid rice population. Forty-five double haploid lines derived from reciprocal double crossing, i.e. IR54/Parekaligolara//Bio110/ Markuti, were phenotypically screened in high Fe wetland rice field at Taman Bogo Experimental Station, Lampung. Molecular analysis performed using STS markers. The results of the association between the genetic and phenotypic analysis showed that there were three markers, i.e. OsIRT1, OsIRT2, and OsFRO2, associated with iron tolerance trait in rice. The markers have potential as selection markers for iron toxicity tolerant lines.